DESIGNED THE DIGITAL SERVICE AS REVISIT INTENTION PROGRAM DURING PANDEMIC FOR THE BEAUTY SALON - Wenny Wenny; Agustina Fitrianingrum (Universitas Internasional Batam, 2022)
Beauty salon is one of the very sensitive industries during the pandemic Covid-19. It is because there is almost no social distancing when it delivers services. Both the consumers and staffs are at a high risk of covid-19 transmission. Due to this urgent situation, the project to save the business in beauty services has been designed. The project implemented at Melati Salon & Sulam which serves a semi-permanent makeup relies on digital technology. To fulfill the requirements of social distancing but still prioritize the convenience of customers, the digital service is one the most possible programs to be implemented. The WhatsApp Business platform is not sufficient to accommodate the need of the salon due to the lack of features offered. The project is introducing the online booking appointment system. Setmore platform helps online ordering more practical to use than offline bookings. The training was conducted for employees. It has been implemented for 3 months. The positive result shows that the number of customers who make online booking is increasing and the employee feel the work is more efficient